Addiction, Anhedonia, and Comorbid Mood Disorder. A Narrative Review - Destoop, Marianne; Morrens, Manuel; Coppens, Violette; Dom, Geert (Frontiers in Psychiatry, 2019)
Background: Recently anhedonia has been recognized as an important Research Domain Criterion (RDoC) by the National Institute of Mental health. Anhedonia is proposed to play an essential role in the pathogenies of both addictive and mood disorders, and possibly their co-occurrence with a single individual. However, up to now comprehensive information about anhedonia concerning its underlying neurobiological circuitries, the neuro-cognitive correlates, and their role in addiction, mood disorder, and co-morbidity remains scarce. Aim In this literature review of human studies, we bring together the current state of knowledge with respect to anhedonia in its relationship with Disorders in the Use of Substances and the co-morbidity with mood disorders. Method A PubMed search was conducted using the following search terms: (Anhedonia OR Reward Deficiency) AND ((Drug Dependence OR Abuse) OR Alcohol OR Nicotine OR Addiction OR Gambling OR (Internet Gaming)). Thirty-two articles were included in the review. Results Anhedonia is associated with substance use disorders and their severity and is especially prominent in DUS with co-morbid depression. Anhedonia may be both a trait and a state dimension in its relation to DUS and tends to impact DUS treatment outcome negatively.